PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KETERAMPILAN MENULIS NASKAH DRAMA SISWA KELAS VIII SMP NEGERI 10 PADANG - Ruhanda, Yola; Tamsin, Andria Catri; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2016)
ABSTRACT This research aims to (1) describe grade ability in writing one act plays of students class VIII SMP Negeri 10 Padang without application cooperative learning TPS type, (2) describe grade ability in writing one act plays of students class VIII SMP Negeri 10 Padang with application cooperative learning TPS type, (3) describe the effect of the use of cooperative learning TPS type, toward students’ ability in writing one act plays of students class VIII SMP Negeri 10 Padang . The type of this research is quantitative research done using experimental design. There are three results of the research are (1) the students’ ability in writing one act plays without application cooperative learning TPS type at class VIII SMP Negeri 10 Padang is more fairly and grades LdC with average 74,51, (2) the students’ ability in writing one act plays with application cooperative learning TPS type at class VIII SMP Negeri 10 Padang is good and grades B with average 83,67, and (3) based on t-test, alternative hypothesis (H1) is gained at the significant phase 95% and degrees of freedom (df) = (n1+n2)-2 because tcount> t-table (4,10>1,70). Kata kunci : pengaruh, kooperatif, think pair share (TPS), dan naskah drama